The reallocation effects of COVID-19: Evidence from venture capital investments around the world - Bellucci, Andrea; Borisov, Alexander; Gucciardi, Gianluca; Zazzaro, Alberto (Journal of Banking & Finance, 2023)
We examine possible reallocation effects generated by the COVID-19 outbreak by analyzing the patterns of venture capital (VC) investments around the globe. Using transaction-level data and exploiting the staggered nature of the spread of the virus, we document a shift in VC portfolios towards firms developing technologies relevant to an environment of social distancing and health pandemic concerns. A difference-in-differences analysis estimates significant increases in invested amount and number of deals in such areas. We show heterogenous effects related to the experience of VC investors, as well as their size and organizational form.